Understanding Lineage Plasticity as a Path to Targeted Therapy Failure in EGFR-Mutant Non-small Cell Lung Cancer - Shaurova, Tatiana; Zhang, Letian; Goodrich, David W.; Hershberger, Pamela A. (Frontiers in Genetics, 2020)
Somatic alterations in the epidermal growth factor receptor gene (EGFR) result in aberrant activation of kinase signaling and occur in ~15% of non-small cell lung cancers (NSCLC). Patients diagnosed with EGFR-mutant NSCLC have good initial clinical response to EGFR tyrosine kinase inhibitors (EGFR TKIs), yet tumor recurrence is common and quick to develop. Mechanisms of acquired resistance to EGFR TKIs have been studied extensively over the past decade. Great progress has been made in understanding two major routes of therapeutic failure: additional genomic alterations in the EGFR gene and activation of alternative kinase signaling (so-called “bypass activation”). Several pharmacological agents aimed at overcoming these modes of EGFR TKI resistance are FDA-approved or under clinical development. Phenotypic transformation, a less common and less well understood mechanism of EGFR TKI resistance is yet to be addressed in the clinic. In the context of acquired EGFR TKI resistance, phenotypic transformation encompasses epithelial to mesenchymal transition (EMT),transformation of adenocarcinoma of the lung (LUAD) to squamous cell carcinoma (SCC) or small cell lung cancer (SCLC). SCLC transformation, or neuroendocrine differentiation, has been linked to inactivation of TP53 and RB1 signaling. However, the exact mechanism that permits lineage switching needs further investigation. Recent reports indicate that LUAD and SCLC have a common cell of origin, and that trans-differentiation occurs under the right conditions. Options for therapeutic targeting of EGFR-mutant SCLC are limited currently to conventional genotoxic chemotherapy. Similarly, the basis of EMT-associated resistance is not clear. EMT is a complex process that can be characterized by a spectrum of intermediate states with diverse expression of epithelial and mesenchymal factors. In the context of acquired resistance to EGFR TKIs, EMT frequently co-occurs with bypass activation, making it challenging to determine the exact contribution of EMT to therapeutic failure. Reversibility of EMT-associated resistance points towards its epigenetic origin, with additional adjustments, such as genetic alterations and bypass activation, occurring later during disease progression. This review will discuss the mechanistic basis for EGFR TKI resistance linked to phenotypic transformation, as well as challenges and opportunities in addressing this type of targeted therapy resistance in EGFR-mutant NSCLC.